UTILIZATION OF NORTH SUMATRA LOCAL CULTURE IN BIOLOGY LEARNING BASED ON 21ST CENTURY COMPETENCIES AND SKILLS - Lubis, Siti Rahmah; Mahriyuni, Mahriyuni; Akrim, Akrim (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2025)
This study aims to examine the utilization of North Sumatra local culture as a learning resource in learning biology based on 21st century competencies and skills. The research method used was descriptive qualitative with a case study approach, involving observation, interviews with teachers and traditional leaders, and document analysis. The results revealed that local cultural elements such as ethnobotany, traditional agricultural systems, and environmental management wisdom can be effectively integrated into biology materials to improve students' concept understanding, learning motivation, and critical thinking skills. The implementation of local culture-based learning also encourages students' active involvement as well as the preservation of social and ecological values. However, the main challenge lies in the limited competence of teachers and the availability of adequate learning resources. This study recommends the development of local culture-based teaching modules and teacher training to support the sustainability of contextualized and sustainable biology learning. The findings provide an important contribution to the development of learning strategies that integrate local wisdom and 21st century competencies